ANALISIS PERPUTARAN AKTIVA DAN RASIO AKTIVITAS SEBAGAI DASAR PENILAIAN KEUANGAN PADA PT BATAM CYCLECT - Siahaan, Sanyta; L. Tobing, Vargo Christian (LPPM Universitas Putera Batam, 2021)
Analysis of financial statements with various ratios can later become information so that it helps management in making decisions for the future. The purpose of this study was to analyze and assess asset turnover and financial activity ratios at PT Batam Cycle. The method used in this research is quantitative descriptive analysis by calculating the ratio of asset turnover and activity ratio with standard provisions so that conclusions can be drawn with secondary data obtained directly from PT Batam Cycle. The results of research on asset turnover of PT. Batam Cyclect in 2015 was 37% (adequate), 2016 was 18% (very poor), 2017 was 26% (enough), 2019 was 38% (enough) and the activity ratio in 2015 was 51% (very good). ), in 2016 it was 59% (very good), in 2017 it was 151% (very good), in 2018 it was 137% (very good), in 2019 it was 38% (very good). Research conclusion Financial performance appraisal at PT Batam cyclect by using the asset turnover ratio does not enter the criteria or very good category and Financial Performance Assessment at PT Batam Cyclect by using the activity ratio is very good.